FAKTOR PENENTU HARGA SAHAM SEKTOR OTOMOTIF: PERAN KEBIJAKAN DIVIDEN, PROFITABILITAS, UKURAN PERUSAHAAN DAN GROWTH OPPORTUNITY - Oktavia Aqma Roza; Diyan Lestari (LPMP Imperium, 2020)
This study aims to analyze the effect of dividend policy, profitability, firm size, and growth opportunity on stock prices in automotive companies during 2009-2017. This study was performed by 13 automotive companies. The sampling technique used in this research is purposive sampling method. This study has 8 companies. Data are analyzed using panel regression and hypothesis test (t statistic). The result showed that dividend policy does not affect the stock prices while profitability, firm size and growth opportunity had an effect on the stock price.